The motorcycle deaths to passenger car deaths ratio and economic performance: a panel data analysis - Sirajudeen, Abdurrasheed Olayinka; Law, Teik Hua; Wong, Shaw Voon; Ng, Choy Peng (Elsevier, 2022)
The existing literature in road safety revealed that the relationship between motorcycle deaths and per-head income follows a Kuznets or reverse U-curve pattern, whereby motorcycle deaths incline at lower income levels but decline once the per-head income has exceeded a threshold level. The same reverse U-curve relationship was also observed between per-head income and other road injury-related variables, including road deaths, road injuries, as well as road deaths to road injuries ratio. Evidence showed that motorcycles and passenger cars are the dominant vehicle modes and contributed significantly to global road deaths. The main objective of this study is to examine the relationship between the motorcycle deaths to passenger car deaths (MDC) ratio and per-head Gross Domestic Product (GDP). Examining the relationship between the MDC ratio and GDP per capita can be effective in understanding the relative change between motorcycle and passenger car deaths at different economic development stages, as well as identifying appropriate preventive measures. We apply a panel linear regression analysis on a panel of 38 countries over the period 1965–2013. Result demonstrated that there is a reverse U-curve relationship between the MDC ratio and the logarithm of GDP per capita. This implies that, at lower levels of GDP per capita, motorcycle deaths were more prevalent than passenger car deaths, whereas as the level of GDP per capita rises, passenger car deaths became relatively prevalent than motorcycle deaths. Moreover, there is a reverse U-shaped relationship between motorcycle ownership to passenger car ownership ratio (MPC) and the MDC ratio, while a U-shaped relationship exists between relative growth in higher mobility roads as compared to higher accessibility roads (MPA) and the MDC ratio. Based on our results, policies and interventions to reduce motorcycle and passenger car deaths were suggested in the conclusion of the paper.